Corporate Governance and Contingency Theory A Structural Equation Modeling Approach and Accounting Risk Implications - Ghofar, Abdul. (Contributions to Management Science,, 2015)
This book analyzes the determinants and effectiveness of corporate governance in an integrated model drawing on contingency theory and employing structural equation modeling (SEM). Business competition as an environmental factor and strategy as an organizational factor are important determinants of corporate governance, while organizational performance and earnings quality are two dimensions of its effectiveness. This book focuses on the relationship between corporate governance and earnings management, and shows that corporate governance is effective in improving earnings quality and reducing accounting and governance risks. The authors also question the relation between corporate governance and company performance and present results of their analysis in this book.